A New Predictive Model for the Prognosis of MDA5+ DM-ILD - Niu, Qian; Zhao, Li-qin; Ma, Wan-li; Xiong, Liang; Wang, Xiao-rong; He, Xin-liang; Yu, Fan (Frontiers in Medicine, 2022)
Purpose: Analyze clinical information and combine significant parameters to generate a predictive model to achieve a better prognosis prediction of dermatomyositis associated interstitial lung disease with positive melanoma differentiation-associated gene 5 antibody and stratify patients according to prognostic risk factors appropriately. Methods: We retrospectively reviewed 63 MDA5+ DM-ILD patients who were treated in our hospital from January 2018 to January 2021. Our study incorporated most clinical characteristics in clinical practice to explore the associations and predictive functions of clinical characteristics and prognosis. Student’s t-test, Mann-Whitney U test, chi-squared test, Pearson correlation analysis, Cox regression analysis, R, receiver operating characteristics curves and Kaplan-Meier survival curves were performed to identify independent predictors of the prognosis for MDA5+ DM-ILD. Results: In all 63 MDA5+ DM-ILD patients, 44 improved but 19 did not improve. Poor prognosis was found more frequently in elders, clinically amyopathic variant of dermatomyositis, short duration, short interval of DM and ILD, long length of stay, fever, dyspnea, non-arthralgia, pulmonary infection, pleural effusion, high total computed tomography scores, ground-glass opacity, consolidation score, reticular score and fibrosis score, decreased forced vital capacity, forced expiratory volume in 1s, albumin, A/G, glomerular filtration rate and tumor necrosis factor α, high titer of anti-MDA5, proteinuria, high levels of monocyte, lactate dehydrogenase, ferritin, neuron specific enolase and glucocorticoid, antibiotic, antiviral and noninvasive positive pressure ventilation. Multivariate Cox regression analysis demonstrated that duration, fever, PE, TCTs and aspartate transaminase were independent predictors of poor prognosis in MDA5+ DM-ILD patients. The nomogram model quantified the risk of 400-day death as: duration ≤ 4months (5 points), fever (88 points), PE (21 points), TCTs ≥ 10 points (22 points) and AST ≥ 200 U/L (100 points) with high predictive accuracy and convenience. The ROC curve possessed good discriminative ability for combination of fever, PE, TCTs and AST, as reflected by area under curve being 0.954, 95% CI 0.902-1.000, sensitivity and specificity being 84.2% and 94.6% respectively. Conclusion: We demonstrated that duration, fever, PE, TCTs and AST could be integrated together to be independent predictors of poor prognosis in MDA5+ DM-ILD with a highly predictive accuracy.